When more is not better: The effect of the number of learning interventions on the acquisition of process-oriented thinking. Issue 2 (April 2016) - Wollersheim, Jutta; Leyer, Michael; Spörrle, Matthias
Given that process-oriented organizations appear to be more successful than function-oriented organizations, organizations increasingly search for effective ways to implement process orientation internally as they grow from having a functional to a process-oriented structure. In this study, we examine whether increasing the number of learning interventions simultaneously used increases the acquisition of process-oriented thinking. The data ( N  = 304) indicate that increasing the number of learning interventions contributes to learning process-oriented thinking to a certain extent: using one learning intervention increased the acquisition of process-oriented thinking more than using no learning intervention, and two learning interventions contributed more to learning process-oriented thinking than using a single learning intervention. However, by increasing the number of learning interventions to three, this increase in the acquisition of process-oriented thinking could not be further enhanced. More fine-grained analyses revealed that using multiple learning interventions was beneficial for relatively unstructured but cognitively demanding process-related tasks, whereas using multiple learning interventions did not increase learning acquisition for relatively structured but cognitively less-demanding process-related tasks. Our findings provide insights into how process-oriented knowledge should be fostered.